First Record of Glossy IBIS Plegadis falcinellus (Linnaeus, 1758) from a High Altitude Region (Chandratal Wildlife Sanctuary) in Himachal Pradesh, India - Chaudhury, Saurav; Lyngdoh, Salvador (Journal of the Bombay Natural History Society (JBNHS), 2023)
No Abstract.